MONETARY POLICY IN ADVANCED ECONOMIES DURING THE GLOBAL FINANCIAL CRISIS: LESSONS FOR LITHUANIA - Visokavičienė, Birutė (Ekonomika, 2014)
Abstract. The main goal of the research is to develop monetary policy tools and measures enabling to achieve macroeconomic goals of integration into the euro area in the immediate future. It is noted that until the introduction of the euro Lithuania does not have a monetary policy and applies the currency board regime pegging the litas invariably to the euro (hard peg regime). Therefore, it is not only difficult but also risky to try to achieve financial and economic stability in accordance with the relevant Maastricht criteria through fiscal policy measures alone. Monetary policy instruments are necessary to achieve price stability and the overall financial stability. Currently, Lithuania should address the problem of balancing the currency board regime and the Maastricht criteria as a macroeconomic objective through monetary policy tools and measures.The analysis of monetary policies of advanced economies and, first of all, of the euro area reveals the main features of transmission of the monetary policy to a real economy, which can contribute to the successful integration into the euro area. A systemic analysis of the monetary policy is based on monetary and economic theories, laws and patterns, scientific literature and empirical studies. The method used is the logical analysis and systemising of academic literature and modelling of the monetary policy. Such a methodological position enables the justification of the influence of the euro and monetary policy on the future development of the national economy.Key words: monetary policy, euro, exchange rate, inflation, indicators